Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1186/1471-2253-5-10
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled trial of spinal endoscopic adhesiolysis in chronic refractory low back and lower extremity pain [ISRCTN 16558617]

Abstract: BackgroundPostoperative epidural fibrosis may contribute to between 5% to 60% of the poor surgical outcomes following decompressive surgery. Correlations have been reported between epidural scarring and radicular pain, poor surgical outcomes, and a lack of any form of surgical treatment. The use of spinal endoscopic adhesiolysis in recent years in the management of chronic refractory low back and lower extremity pain has been described.MethodsA prospective, randomized, double-blind trial was conducted to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(125 citation statements)
references
References 68 publications
4
115
0
4
Order By: Relevance
“…Interestingly, the decreased mRNA 'early growth response (EGR1)' was reported to be closely related to fibrosis in many previous studies [32][33][34][35]. Therefore, we thus leads to poor outcomes in spinal surgeries [1][2][3][4]. Previous reports have showed that epidural fibrosis was closely related to fibroblasts activation and collagen overproduction [27].…”
Section: Taurine Decreased Expression Of Egr1 Both In Vivo and In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the decreased mRNA 'early growth response (EGR1)' was reported to be closely related to fibrosis in many previous studies [32][33][34][35]. Therefore, we thus leads to poor outcomes in spinal surgeries [1][2][3][4]. Previous reports have showed that epidural fibrosis was closely related to fibroblasts activation and collagen overproduction [27].…”
Section: Taurine Decreased Expression Of Egr1 Both In Vivo and In Vitromentioning
confidence: 99%
“…Epidural fibrosis has been demonstrated to contribute to up to 5% of poor surgical outcomes following decompressive surgery [4]. Given this, during the past decades, there has been an increasing interest in development of effective drugs to prevent the formation and adherence of the tissue to the neural elements is of importance in improving surgical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…El estudio de mayor relevancia epidemiológica en este apartado fue el publicado por Manchikanti y cols. (8), en el cual se evaluó la efectividad de la lisis de adherencias por vía endoscópica en dolor lumbar crónico en un estudio clínico controlado aleatorizado. Cabe mencionar que aunque este estudio no utilizó un control con placebo, sí se trató de un estudio aleatorizado, doble ciego, con control por equivalencia, utilizando un diseño de controles activos.…”
Section: Inyección Epidural De Esteroides Lisis De Adherencias Lisis unclassified
“…De igual manera, cuando el dolor es de características radiculares, los resultados a largo plazo son más favorables que cuando se trata de dolor axial o inespecífico (15). Por otro lado, consideramos que a todo paciente que se realice epiduroscopia con fines terapéuticos se debe realizar lisis de adherencias y aplicación dirigida de esteroides (recomendación 1-B, nivel de evidencia II-1) (8). Se debe aclarar, sin embargo, que el método mediante el cual se realice la lisis de adherencias no tiene impacto en los resultados (recomendación 2-C, nivel de evidencia II-1) (10,13 (20) en los pacientes en quienes se tornan sintomáticas el tratamiento con epiduroscopia se ha convertido en una herramienta importante en el armamentario terapéutico del cirujano.…”
Section: Conclusionesunclassified
“…Most often steroids and local anesthetics are injected into the epidural space after adhesiolysis [12,13,20] while other substances such as clonidine [12], hyaluronidase [14,19], ciprofloxacin [14] and ozone [14] have also been used.…”
Section: Methodsmentioning
confidence: 99%